Incidence, Prognostic Factors, and Treatment Impact on Survival in Natural Killer/T-Cell Lymphoma: Population-Based Study in the United States - Yi Zhao; Yi Zhong; Mengqi Xiong; Linlin Huang; Xiujin Ye; Jingsong He (JMIR Formative Research)
Abstract BackgroundNatural killer/T-cell lymphoma (NKTL) is a rare malignancy of mature natural killer/T-cells, predominantly found in Asian and South/Central American populations, with limited studies conducted in Europe and the United States. ObjectiveThe aim of this study is to present an overview of the incidence rate, demographic and clinical characteristics, treatment options, overall survival (OS), and factors influencing OS of NKTL in the United States. MethodsWe used data from the Surveillance, Epidemiology, and End Results 17 database to analyze NKTL cases recorded between 2000 and 2020. In a cohort of 1162 patients with NKTL, we calculated the incidence rates and performed statistical analyses to evaluate OS, the effect of radiotherapy and chemotherapy on survival, and lymphoma-specific survival. ResultsThe mean annual incidence rate of NKTL in the United States was 0.067 per 100,000, with higher rates observed in men compared to women, and an increase noted with age. However, there has been no significant rise in incidence over recent years. Significant racial disparities were observed, with higher incidence rates in non-Hispanic Asian or Pacific Islanders and Hispanic people. The median survival time for patients with NKTL was 21 months, with a 5-year OS rate of 39.5%, which has shown improvement in recent years. Key independent prognostic factors impacting patient survival included age at diagnosis, clinical stage, nasal type presentation, presence of systemic symptoms, and treatment modality. Patients receiving combined radiotherapy and chemotherapy exhibited the best outcomes, with a median OS of 138 months and a 5-year OS rate of 58%. This survival benefit remained consistent even in patients with stage I/localized nasal type lymphoma, achieving a 5-year OS rate of 73.3%. ConclusionsThe incidence of NKTL has remained stable in recent years. Patients with the nasal type generally experience better survival outcomes. The use of combined radiotherapy and chemotherapy appears to enhance survival, though further validation through prospective multicenter clinical trials is necessary.